Neutron-neutron angular correlation in 252Cf spontaneous fission - Pringle, John Stephen (Department of Physics, 2023)
The angular correlation between prompt neutrons emitted in 252 cf spontaneous fission has been measured. The observed correlation is compared with a theoretical calculation based on the evaporation model of neutron emission. It is found that the evaporation model is unable to account for the observed strong peaking in the n-n angular correlation at small angles. Preliminary calculations show that two of the proposed alternative neutron emission mechanisms, polar emission and "tidal wave" emission, may be able to account for the observed n-n angular correlation.